Edukasi Dampak Merokok dan Upaya Pencegahannya - Effendi, Ida; T. Robertus; Bella, Isa; Prasetyaningsih, Noviani (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Cigarette consumption is one of the main risk factors for many diseases and become the leading cause of death in the world, including in Indonesia. Diseases caused by smoking can be prevented by having good understanding of smoking and its impact on health followed by changes into clean and healthy living behaviors. Community service activities (PkM) were carried out with the aim of improving the health status of PPSU officers in West Cengkareng. Education was held on May 9, 2025 at the Cengkareng Barat sub-district office, West Jakarta. The target of this activity was PPSU officers in the Cengkareng Barat sub-district. Education on the impact of smoking on health and its prevention was provided by presenting information about smoking behavior, health impacts and steps to prevent diseases that can be caused by smoking. A total of 33 participants consisting of 27 male officers (82%) and 6 female officers (18%) participated in this activity. Smoking knowledge of participants was obtained through filling out a questionnaire and obtained good knowledge (88.4%) regarding the impact of smoking on health. With a good understanding, it is hoped that this PkM activity can improve the health status of PPSU officers in the Cengkareng Barat sub-district.